Finance, Control, and Profitability: The Influence of German Banks - Robert S. Chirinko; Julie Ann Elston (Center for Economic Studies and ifo Institute (CESifo), 2003)
Bank intermediated finance has been cited frequently as the preferred means for channeling funds from savers to firms. Germany is the prototypical economy where universal banks allegedly exert substantial influence over firms. Despite frequent assertions about the considerable power of German banks and the advantages of a bank relation, empirical support is mixed. With a unique dataset and a focus on the fragility/sturdiness of inferences, this paper evaluates German bank influence in terms of three hypotheses: 1) do bank influenced firms enjoy lower finance costs? [No]; 2) is bank influence a solution to control problems? [Yes]; 3) do bank influenced firms have higher profitability? [No]. Coupled with results about the control consequences of concentrated ownership, these results suggest that bank influence serves as a substitute control mechanism, one of several available for addressing corporate control problems.
Keywords: G21; G32; G34; 330; German banks; corporate finance and governance